Numerical exploration of Hall and Dufour effects on rotating MHD natural convection near an infinite vertical plate with ramped boundary conditions using FDM and RSM using combined FDM and RSM approaches - Obulesu Mopuri; Charankumar Ganteda; Rudraravi Kumar Palegari; G. Jaya Lalitha; P. Harikrishna; K. Rajyalakshmi; Vediyappan Govindan; Haewon Byeon; Busayamas Pimpunchat (International Journal of Thermofluids)
This study investigates the effects of ramped parameters, diffusion thermo effects, radiation and heat absorption, Soret, and Hall effects on rotating MHD free convective flow under simultaneous ramped boundary conditions. The governing equations are transformed into dimensionless form and solved using an explicit finite difference method (FDM), with numerical results for velocity, temperature, concentration, viscous drag, heat, and mass transfer rates analyzed using MATLAB. Results show that increasing ramped parameters enhances momentum, heat, and mass transfer rates, with a novel observation of increased fluid velocity under stronger magnetic constraints. Additionally, the finite response method (FRM) is proposed to optimize parameter interactions, enabling efficient modeling and prediction of outcomes for variations beyond those tested in the FDM. This integration enhances understanding of sensitivities and optimal conditions in fluid behavior under simultaneous ramped constraints.